Japanese encephalitis circulation pattern in swine of northern Vietnam and consequences for swine's vaccination recommendations. Issue 6 (8th May 2018) - Ruget, A.‐S.; Beck, C.; Gabassi, A.; Trevennec, K.; Lecollinet, S.; Chevalier, V.; Cappelle, J.
Summary: Japanese encephalitis (JE) is the largest worldwide cause of infectious encephalitis in humans and is caused by a mosquito‐borne flavivirus. JE transmission cycle involves Culex mosquitoes, pigs and aquatic birds as principal vertebrate amplifying hosts. JE infection is responsible for reproductive disorder in pigs when occurring after sexual maturity. In tropical areas, JE is endemic and the majority of pigs get infected before the age of 6 months. However, in subtropical areas, pigs may be infected after sexual maturity and thus experience clinical signs, inducing economic loss. The study aimed at better characterizing the influence of seasonal temperature variations (through estimates of degree days, DD) on JE circulation in pigs in subtropical area and inferring on the potential impact on JE symptomatic infection in reproductive pigs. Six hundred and forty‐one pig's sera sampled in northern Vietnam were analysed for Japanese encephalitis virus (JEV) by pan‐flavivirus ELISA. A subset of 108 ELISA‐positive samples, representative of each sampling occasion, were confirmed by JEV neutralization test compared with West Nile virus neutralization test. We modelled the seroprevalence of pigs according to a DD variable using a generalized additive model. We then predicted the age of infection in pigs according to their month of birth, using averaged temperature data over 10 years. The model predicts that only 80 percentage of pigs born between July and September will be protected against JEV when reaching sexual maturity contrary to the rest of the year when almost all pigs will seroconvert before sexual maturity. In subtropical area such as northern Vietnam, pigs could thus show symptomatic infection due to JE, and consequently reproductive disorders. Vaccination of future breeder pigs in epidemic areas could avoid the occurrence of JE‐associated reproductive disorders.